Implementasi Metode Syair Dalam Pembelajaran Bahasa Arab - Fadlin, Iswan (Ameena Journal, 2023)
The Poetry Method is a method of learning Arabic that can be applied to students in Madrasahs and students in Islamic boarding schools. In the world of Islamic boarding schools, there is a special discipline for studying Arabic literature, better known as Balaghah science. In its very broad discussion, studying Arabic literature is very helpful in growing the attraction of learning Arabic, which has been difficult to understand. Some Arabic language books taught to intermediate level madrasah students focus more on grammatical discussions, thus affecting students' understanding of Arabic, which seems difficult to learn. This article utilizes the method of library research. The implementation of the poetry method should start from an early age by introducing Arabic poetry and even barzanji which are often popularized in the form of nasheed songs, thus creating interest in learning Arabic. Parents, teachers at schools and Islamic boarding schools and other stakeholders have a big role in implementing the poetry method and must also continue to work together, innovate in introducing the poetry method and be able to formulate answers to all challenges and obstacles in implementing this method in Arabic language learning.